Pentingnya bimbingan dan konseling untuk mengembangkan kecerdasan sosial siswa - Rahim, Maryam; Usman, Irvan; Puluhulawa, Meiske (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2016)
Social intelligence is intelligence that includes group interaction and closely related with social skills. Social intelligence on students in need of assistance in development, including through education programs in schools. The phenomenon is occurring today, school programs tend to be more focused on helping students develop academic potential, and often ignore the development aspects of social intelligence. Students are learn how a good way of learning to pass exams while efforts to improve the social aspect is still limited. A result that occurs from these conditions include: frequent disputes between students, fighting between the school, the low capacity of cooperation in learning activities and daily life, and low empathy. Guidance and counseling as a vehicle to help the personality development of students as a whole, has an important role in developing social intelligence of students through a systematic and continuous. That requires a wide range of supporting components, such as structured programs both annual program and daily programs, guides the implementation of a clear, material services arranged by the theoretical basis of social intelligence, guide the evaluation of specific measures social intelligence, as well as teachers' guidance and counseling/counselor have specific competence in performing services for the development of students' social intelligence.